2005
DOI: 10.1002/cfg.468
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato Sequencing Project, the first cornerstone of the International Solanaceae Project (SOL)

Abstract: The genome of tomato (Solanum lycopersicum) is being sequenced by an international consortium of 10 countries (Korea, China, the United Kingdom, India, The Netherlands, France, Japan, Spain, Italy and the United States) as part of a larger initiative called the ‘International Solanaceae Genome Project (SOL): Systems Approach to Diversity and Adaptation’. The goal of this grassroots initiative, launched in November 2003, is to establish a network of information, resources and scientists to ultimately tackle two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(73 citation statements)
references
References 33 publications
(25 reference statements)
0
72
0
1
Order By: Relevance
“…Others are prized for their medicinal, poisonous, or psychotropic effects and are the source of drugs such as atropine, scopolamine, and hyoscyamine (OksmanCaldentey, 2007). As a result, the Solanaceae has been the focus of considerable research, including genome sequencing projects for both tomato and potato (Mueller et al, 2005;Mullins et al, 2006).…”
mentioning
confidence: 99%
“…Others are prized for their medicinal, poisonous, or psychotropic effects and are the source of drugs such as atropine, scopolamine, and hyoscyamine (OksmanCaldentey, 2007). As a result, the Solanaceae has been the focus of considerable research, including genome sequencing projects for both tomato and potato (Mueller et al, 2005;Mullins et al, 2006).…”
mentioning
confidence: 99%
“…An expanding range of molecular and genomics tools are available for tomato, including facile transformation (Klee et al, 1991), a large EST collection (Van der Hoeven et al, 2002), oligonucleotide-based arrays (Slocombe et al, 2008;Wang et al, 2009), emerging genome sequence information (Mueller et al, 2005a(Mueller et al, , 2005b, and a wide range of phenotyping (Causse et al, 2004) and metabolite profiling (Tikunov et al, 2005;Schauer et al, 2006;Fraser et al, 2007) technologies. Very recently, a prepublication tomato genome sequence was made available by the International Tomato Genome Sequencing Consortium (http:// solgenomics.net/).…”
mentioning
confidence: 99%
“…Since the beginning of 1990s, the contribution of molecular markers and maps to tomato breeding and gene identification has been widely documented (Foolad, 2007;Frary et al, 2005;Gupta et al, 2009), and more than 15.000 different markers are collected in the SGN database, where markers can be searched by name, chromosome position and mapping population. Moreover, cytological and cytogenetic maps are also available, as well as a detailed physical map, which was the foundation for the tomato genome sequencing project (Mueller et al, 2005). Contemporarily, gene expression analyses performed on different tissues and developmental stages, as well as on genotypes that differ in their answer to environmental stimuli, have dramatically raised the number of ESTs available at various websites.…”
Section: Genetic and Genomic Resourcesmentioning
confidence: 99%
“…Since tomato is considered the model species among the Solanaceae, these novel techniques have been also exploited for other economically important crops, such as potato, pepper, and eggplant. Moreover, due to the high sinteny existing among Solanaceae species, tomato was chosen as reference genome to be completely sequenced by the International Tomato Genome Sequencing Consortium at the end of the year 2003 (Mueller et al, 2005). Molecular comparative mapping studies revealed a high level of conserved gene content and order within this family (Wu & Tanksley, 2010), as well as within other families (i.e grasses, crucifers, legumes).…”
mentioning
confidence: 99%